2022
DOI: 10.3390/ijms232415545
|View full text |Cite
|
Sign up to set email alerts
|

Zingiber officinale Rosc. in the Treatment of Metabolic Syndrome Disorders—A Review of In Vivo Studies

Abstract: Inflammation is a protective reaction of the innate immune system as a response to imbalances caused by a specific stimulus, a disease or a pathogen. A prolonged inflammatory condition may lead to the development of metabolic syndrome, which affects more than one-fourth of the world’s population. This condition leads to the development of multi-organ disorders based on disrupted blood lipid and sugar levels, hypertension and oxidative stress. The review aims to present Zingiber officinale Rosc. as a plant that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Mahluji et al (2013) demonstrated in their study that Z. officinale can reduce insulin levels in patients with type 2 diabetes. Additionally, Z. officinale supplementation shows supportive effects in the treatment of inflammatory disorders and metabolic syndrome (Gumbarewicz et al 2022).…”
Section: Fidelity Level (Fl) Of Medicinal Plantsmentioning
confidence: 99%
“…Mahluji et al (2013) demonstrated in their study that Z. officinale can reduce insulin levels in patients with type 2 diabetes. Additionally, Z. officinale supplementation shows supportive effects in the treatment of inflammatory disorders and metabolic syndrome (Gumbarewicz et al 2022).…”
Section: Fidelity Level (Fl) Of Medicinal Plantsmentioning
confidence: 99%
“…Numerous researchers studied the effects of different natural extracts ( Aloe vera , Zingiber officinale , Tabernaemontana divaricata , etc.) on the pathophysiological mechanisms of DM, showing beneficial effects on hyperglycemia [ 3 , 4 , 5 ] and on diabetes-related cardiovascular impairments [ 6 ].…”
Section: Introductionmentioning
confidence: 99%